Morphophysiological responses of black soybean to nitrogen-fixing bacterial inoculants from diverse agroecosystems - FAIRUS HISANAH HIBATULLAH; USAMA YASEEN; FARHAN AHMAD; FIQRIAH HANUM KHUMAIRAH; AGUNG KARUNIAWAN; EMMA TRINURANI SOFYAN; ANNE NURBAITY; TUALAR SIMARMATA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Hibatullah FH, Yaseen U, Ahmad F, Khumairah FH, Karuniawan A, Sofyan ET, Nurbaity A, Simarmata T. 2026. Morphophysiological responses of black soybean to nitrogen-fixing bacterial inoculants from diverse agroecosystems. Biodiversitas 27 (1): d270133. https://doi.org/10.13057/biodiv/d270133. Black soybean (Glycine max) is a legume crop of high nutritional and economic value, especially in sustainable agricultural systems. Its productivity, however, is often limited by nutrient-deficient soils. We hypothesized that inoculation with Symbiotic Nitrogen-Fixing Bacteria (SNFB) sourced from diverse agroecosystems could enhance morphophysiological performance under controlled conditions. This study aimed to evaluate the morphophysiological responses of black soybean to inoculation with SNFB isolated from diverse agroecosystems. The study comprised (i) isolation and phenotypic characterization of SNFB strains and (ii) greenhouse evaluation using a randomized complete block design with six bacterial treatments (BJ-H1, BJ-H2, BJ-H3, BJ-H4, BJ-H5, and BJ-H6) and an uninoculated control, each with four replicates. Parameters measured included plant height, chlorophyll content, fresh and dry biomass, and nodulation. Analysis of Variance (ANOVA) followed by post-hoc comparisons (p<0.05) revealed that BJ-H5 significantly increased plant height (2.41%), chlorophyll content (14.7%), fresh shoot biomass (59.33%), and dry shoot biomass (21.11%) relative to the control, BJ-H2 and BJ-H3 induced the highest nodulation, indicative of enhanced nitrogen fixation. Correlation and principal component analyses demonstrated robust positive associations between inoculation treatments and growth traits. These findings provide statistically substantiated evidence that targeted SNFB inoculation, particularly with strain BJ-H5, represents a viable biofertilizer strategy for improving black soybean productivity on marginal or degraded soils, thereby reducing dependence on synthetic nitrogen inputs and supporting sustainable crop intensification.